Factors Affecting the Acceptance to Use the AI in Cyber Security Technology - Khehaban, Supawat; Buranasiri, Jiroj (Suan Dusit Graduate School Academic Journal, 2026)
This research aimed to (1) study the factors affecting the acceptance to use the AI in cyber security technology, and (2) identify the component of factors affecting the acceptance to use the AI in cyber security technology. This research was quantitative research by collecting data from 500 personnels responsible in cyber security of the listed companies using digital and information technology in their business operations. The sample were selected by using purposive sampling. The questionnaire was used as the research instrument for data collection. The Index of Item-Objective Congruence (IOC) was between 0.60 and 1.00 and the reliability analysis of the overall test indicated Cronbach’s Alpha Coefficient (α) at 0.95. The statistics for data analysis were frequency distribution, percentage, mean, standard deviation and structural equation model. The study found that (1) factors affecting the acceptance to use the AI in cyber security technology included organizational context, expectation for use, social influence, perceived trust and perceived usefulness. The factor loadings were 0.393, 0.611, 0.930, 0.244, and 0.689, respectively, with the predictive power of 80.6 (R2= .806) (2) The results of the exploratory factor analysis found that factors affecting the acceptance to use the AI in cyber security technology consisted of nine factors, twenty-five groups of components. The results of model fit found that the research model was consistent with empirical data, with CMIN/df = 2.410, GFI = 0.936, AGFI = 0.927 and RMSEA 0.033.